A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini) - Bezark, Larry G.; Santos-Silva, Antonio; Nascimento, Francisco E. De L. (Zootaxa, 2018)
Three new species of Dorcasta Pascoe, 1858 are described: D. birai, from Brazil (Goiás); D. parkeri, from Mexico, Nicaragua and Costa Rica; and D. rifkindi, from Mexico and Panama. Additionally, D. dasycera, D. borealis, and D. crassicornis are redescribed. Dorcasta crassicornis is recorded from Mexico, Guatemala and Costa Rica, and D. borealis is recorded from Costa Rica. New state records for Mexico are provided for Dorcasta cinerea. A key to the known species of Dorcasta is provided.